2018
DOI: 10.1111/evj.12844
|View full text |Cite
|
Sign up to set email alerts
|

Vertical movement symmetry of the withers in horses with induced forelimb and hindlimb lameness at trot

Abstract: SummaryBackgroundThe main criteria for lameness assessment in horses are head movement for forelimb lameness and pelvic movement for hindlimb lameness. However, compensatory head nod in horses with primary hindlimb lameness is a well‐known phenomenon. This compensatory head nod movement can be easily misinterpreted as a sign of primary ipsilateral forelimb lameness. Therefore, discriminating compensatory asymmetries from primary directly pain‐related movement asymmetries is a prerequisite for successful lamene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 21 publications
11
66
1
Order By: Relevance
“…We assume that the vertical movement of the sternum can be influenced by both hind-and forelimbs. It has been shown that asymmetric movement of the pelvis translates to asymmetric movement of the wither on the contralateral side due to compensatory mechanisms [29]. On the other hand, SD min could also reflect asymmetric vertical loading of the forelimbs.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the vertical movement of the sternum can be influenced by both hind-and forelimbs. It has been shown that asymmetric movement of the pelvis translates to asymmetric movement of the wither on the contralateral side due to compensatory mechanisms [29]. On the other hand, SD min could also reflect asymmetric vertical loading of the forelimbs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on non-pathological sources of asymmetry at trot [ 1 , 18 19 ], in which the vertical excursions of head, withers and/or pelvis are commonly used for symmetry evaluation. Withers symmetry has been shown to be the most direct indication of asymmetry in the forelimbs that is least prone to confounding influences [ 20 ]. However, the walk has been largely neglected and relatively little is known about inherent asymmetries in this gait.…”
Section: Introductionmentioning
confidence: 99%
“…That pattern is also found in many (not all) clinically hind limb lame horses [ 6 , 13 ]. The opposite-sided changes in PDmin and PDmax found here suggest that horses move mechanically differently immediately after being fitted with an orthotic lift–an artificial lengthening of one of the hind limbs–compared to an induced (painful) lameness [ 14 ] or indeed differently to common patterns seen in naturally asymmetrical horses [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ‘law of sides’ [ 13 ] relates a concurrent ipsilateral head and pelvic asymmetry to an increased likelihood of a primary hind limb lameness and a contralateral asymmetry to a primary forelimb lameness. Adding measurement of withers movement asymmetry into a gait assessment has shown good discriminative potential between induced forelimb lameness (head and withers movement asymmetry same-sided) and induced hind limb lameness (head and withers movement asymmetry of opposite direction) [ 14 ]. Synchronous measurement of head, withers and pelvic movement hence appears to be a workable compromise between in-field applicability (measurement with cameras or inertial measurement units rather than direct measurement of force with force platforms) and providing sufficiently accurate and precise measurements [ 15 , 16 ] allowing insights into the fundamental mechanics related to force asymmetry in lame horses.…”
Section: Introductionmentioning
confidence: 99%